(untitled) (Geography and Tourism, 2018)
The work relates to navigation conditions of the Lower Don. The research was performed on hydrological and sediment regimes of the Don River, downstream of the Kochetovsky hydraulic engineering complex. The impact of the planned Bagaevskiy Dam construction on hydraulic characteristics of the flow and deformation of the riverbed was also assessed. Materials collected during engineering and hydrometeorological surveys, the results of mathematical modelling and hydraulic studies completed as part of the design works on the facility – “The Bagaevskiy Dam construction on the Don River” – were used as input data.